Transformasi Pembelajaran Melalui Implementasi Kurikulum Merdeka Di Sekolah Dan Era Society 5.0 - Windy Septiana; Muhammad Yahya; Ernawati (CV. Insight Publisher, 2024)
This study aims to explore the implementation design of the Merdeka Curriculum at SMK Negeri 1 Maros, identify who is involved in its development, and outline the obstacles and challenges faced in its implementation. This research uses a qualitative method with data collection techniques through in-depth interviews with several teachers at SMK Negeri 1 Maros. The research findings show that the implementation design of the Merdeka Curriculum at SMK Negeri 1 Maros has similarities with the structure of the 2013 Curriculum, with the addition of the Pancasila profile as a compulsory subject. Those involved in developing this design include the principal, subject teachers, and the school curriculum team. This study also found several obstacles and challenges in implementing the Merdeka Curriculum, including the need for adaptation for teachers and limited resources